Indonesian Students Intellectual Internship Overseas - Agus Joko Pitoyo; Kirana Putri Prastika (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2019)
Indonesia is classified as developing country which still have low level of national education. One of the way to improve the level of education happening in this era is by studying abroad. There are lot of universities in Indonesia that already establish cooperation with foreign universities. This cooperation helps Indonesia student get the accessibility to join study abroad program. This paper has two objectives. The first one is to know the development of studying abroad program conducted by Indonesian student spatially and temporarily. The second one is to know Indonesian student’s perspectives about study abroad program from their level of satisfaction. This paper uses primary and secondary data to analyze this issue. This primary data was taken from questionnaire through 14 respondents and the secondary data was taken from UNESCO statistical data and news. The results of the paper show that the spatial distribution of Indonesian student international mobility varies from Asian, European, Middle Eastern, and American countries. Indonesian student tends to visit development economy countries rather than developing economy countries. According to the data collected from 14 respondents, Japan is the most visited country and also shows that the temporal development of this international mobility is growing from 2013 to 2019. This positive development is reinforced by the high level of satisfaction according to 14 respondents. These respondents had joined 23 program and only two programs were not satisfactory for two respondents.